Chemical proteomics reveals new targets of cysteine sulfinic acid reductase. (November 2018) - Akter, Salma; Fu, Ling; Jung, Youngeun; Conte, Mauro; Lawson, J.; Lowther, W.; Sun, Rui; Liu, Keke; Yang, Jing; Carroll, Kate
Abstract Cysteine sulfinic acid orS -sulfinylation is an oxidative post-translational modification (OxiPTM) that is known to be involved in redox-dependent regulation of protein function but has been historically difficult to analyze biochemically. To facilitate the detection ofS -sulfinylated proteins, we demonstrate that a clickable, electrophilic diazene probe (DiaAlk) enables capture and site-centric proteomic analysis of this OxiPTM. Using this workflow, we revealed a striking difference between sulfenic acid modification (S -sulfenylation) and theS -sulfinylation dynamic response to oxidative stress, which is indicative of different roles for these OxiPTMs in redox regulation. We also identified >55 heretofore-unknown protein substrates of the cysteine sulfinic acid reductase sulfiredoxin, extending its function well beyond those of 2-cysteine peroxiredoxins (2-Cys PRDX1–4) and offering new insights into the role of this unique oxidoreductase as a central mediator of reactive oxygen species–associated diseases, particularly cancer. DiaAlk therefore provides a novel tool to profileS -sulfinylated proteins and study their regulatory mechanisms in cells. An electrophilic diazene probe (DiaAlk) enables capture and proteomic analysis of cysteineS -sulfinylation modifications, thus illuminating dynamic responses to oxidative stress and enabling the identification of new substrates of sulfiredoxin.